2018
DOI: 10.1007/s11258-018-0898-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the alien plant Impatiens glandulifera on species diversity of invaded vegetation in the northern foothills of the Tatra Mountains, Central Europe

Abstract: The impact of exotic annual Impatiens glandulifera on invaded European vegetation is ambiguous; there are studies reporting considerable negative as well as weak or even no impact of this invader on species richness and diversity of the invaded communities. The effect of invasion by I. glandulifera on species richness, diversity and the composition of resident vegetation was studied in the northern foothills of the Tatra Mountains in southern Poland. Two approaches were used: comparing diversity measures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…German and European Union nature conservation authorities emphasize the impact on diversity and threat to other species (European Union 2014, Nehring et al 2015). Taking this study and all available ones into account, the impact of I. glandulifera on plant species diversity can be rated to be relatively low (Hejda and Pyšek 2006, Hejda et al 2009, Diekmann et al 2016, Čuda et al 2017 even if some studies showed stronger effects (Hulme and Bremner 2006, Cockel et al 2014, Kiełtyk and Delimat 2019. Indeed, we found a negative impact on the dominant natives, U. dioica and F. ulmaria, but they are in general very common and widespread in Central Europe and thus not expected to be threatened (Schreiber 1958, Weber 1995.…”
Section: Assessment Of the Invasiveness Of Impatiens Glanduliferamentioning
confidence: 76%
“…German and European Union nature conservation authorities emphasize the impact on diversity and threat to other species (European Union 2014, Nehring et al 2015). Taking this study and all available ones into account, the impact of I. glandulifera on plant species diversity can be rated to be relatively low (Hejda and Pyšek 2006, Hejda et al 2009, Diekmann et al 2016, Čuda et al 2017 even if some studies showed stronger effects (Hulme and Bremner 2006, Cockel et al 2014, Kiełtyk and Delimat 2019. Indeed, we found a negative impact on the dominant natives, U. dioica and F. ulmaria, but they are in general very common and widespread in Central Europe and thus not expected to be threatened (Schreiber 1958, Weber 1995.…”
Section: Assessment Of the Invasiveness Of Impatiens Glanduliferamentioning
confidence: 76%
“…The results thus indicate that increased palatability due to increased temperature may contribute to reduced performance in cold-adapted species under future climate warming, while at the same time, these changes in palatability may increase the success of warm-adapted species 81 . Invasion success of warm-adapted species might be further strengthened by strong effects on diversity of native communities as found for another Impatiens species 82,83 .…”
Section: Importance Of Leaf Traits For Leaf Palatabilitymentioning
confidence: 95%
“…Each plant can produce hundreds of seeds which are forcibly ejected up to 7 m away from the parent plant, leading to the development of dense monospecific stands. These monocultures of Himalayan balsam can have negative impacts on native biodiversity, by altering the soil microbial, invertebrate and plant communities (Tanner et al 2013(Tanner et al , 2014Gaggini et al 2018;Kiełtyk and Delimat 2019). As an annual plant, Himalayan balsam stands die back in the autumn and this may have impacts on soil erosion and siltation (Greenwood et al 2020).…”
Section: Examples Of Some Benefit Sharing Case Studiesmentioning
confidence: 99%